Integrated Energy Management and Grid Support Functions for Multi-Type RES and EV Enhanced Microgrid Operations - Turkoglu, Aligul Selim; Cicek, Alper; Erdinc, Ozan (IEEE, 2025)
This paper presents a comprehensive energy management model tailored for microgrid optimization, focusing on enhanced integration of Renewable Energy Sources (RESs) into the distribution system. The model encompasses a microgrid hosting RESs, catering to an all-in-one electric vehicle (EV) station which can accommodate plug-in EVs, battery swappable EVs, and fuel cell EVs. Augmented by hydrogen storage, electrolyzers, and flexible loads for demand response applications, the RESs are adept at active and reactive power modulation within the grid. Notably, the study discusses the grid impact of diverse objective functions concerning voltage deviation minimization via reactive power support and active power curtailment (APC), evaluating microgrid profitability within a bi-level framework by considering carbon cost and APC penalty. The paper concludes by establishing an optimal power flow model to test the efficacy of the proposed framework. The study results with a zero APC, a better voltage profile accommodated by a fair microgrid profit even without a direct focus on APC minimization.
Keywords: All-in-one electric vehicle station; demand response; energy management strategy; microgrid; optimal power flow; CONGESTION MANAGEMENT; TRANSACTIVE ENERGY; ELECTRIC VEHICLES; NETWORK; Computer Science; Science & Technology - Other Topics; Energy & Fuels; Engineering